The EPA guidance on suicide treatment and prevention needs to be adjusted to fight the epidemics of suicide at the North Pole area and other autochthonous communities - Charlier, P.; Malaurie, J.; Wasserman, D.; CARLI, Vladimir; SARCHIAPONE, Marco; Dagenais Everell, C.; Herve, C. (European Psychiatry, 2017)
More and more, youth suicide in the Inuit community is gaining importance, with a frequency in Greenland rising from 14.4 (1960–64) to 110.4 per 100,000 person-years (2010–11). The huge cultural/educational changes during the last 20 years and the role of globalization, especially of the occidental influence on this community may be at the origin of such an “epidemics” of suicide in this cultural region. Recently, a political organization representing the Inuit community in Canada (ITK for Inuit Tapiriit Kanatami) launched a National Inuit Suicide Prevention Strategy (NISP) based on the specificities of this community in comparison to the occidental civilization. In fact, not only the Canadian Inuit community is concerned by this epidemics of suicide, but also many other autochthonous groups. In this context, the European Psychiatric Association (EPA) guidance on suicide treatment and prevention needs to be adjusted to autochthonous individuals’ needs.